BOEKAANKONDIGINGS / BOOK NOTICES - Lategan, Bernard C. (Scriptura, 1985)
Beek, M A. 1984. Kommentaar: Prediker/Hooglied. G F Callenbach.Collins, John J. 1984. Commentary: Daniel - With an introduction to Apocalyptic Literature. Eerdmans.Van der Woude, A S. 1984. Kommentaar: Zacharia. G F Callenbach.Bock, Paul (ed). 1984. Signs of the Kingdom - A Ragaz Reader. Eerdmans.Longenecker, Richard N. 1984. New Testament social ethics for today. Eerdmans.Vehey, Allan. 1984. The Great Reversal - Ethics and the New Testament. Eerdmans.Walsh, Michael & Davids, Brian (eds). 1984. Proclaiming Justice and Peace. Documents from John XXIII to John Paul II. Collins.Hayes, John H & Prussner, Frederick C. 1985. Old Testament Theology: its history and development. London: SCM.Neuhaus, Richard John. 1984. The naked public Square - Religion and Democracy in America. Eerdmans. Thurmer, John. 1984. A detection of the trinity. Paternoster.Van de Beek, A. 1984. Waarom? Over lijden, schuld en God. G F Callenbach.Wolters, A M. 1985. Creation regained: Biblical basics for a reformational worldview. Grand Rapids, Michigan: Eerdsmans.Bossy, John. 1985. Christianity in the West. Oxford University Press.Bratt, James D. 1984. Dutch Calvinism in modern America. Eerdmans.De Gruchy, John W. 1984. Bonhoeffer and South Africa. Eerdmans.Marsden, George (ed). 1984. Evangelicalism and modern America. Eerdmans.